Unexpected reactivity patterns of Ruthenium alkylidenes with N-phosphino-functionalized N-heterocyclic carbene ligands (NHCPs) - Brown, Christopher; Rominger, Frank; Hofmann, Peter (Organometallics, 2014)
N-phosphino-functionalized N-heterocyclic carbene (NHCP) ligands have been evaluated as potential supporting ligands in ruthenium-catalyzed olefin metathesis. Initial density functional theory (DFT) calculations suggested that these NHCP ligands may allow access to neutral 14 valence electron (VE) species—equivalents of the active 14 VE species formed by phosphine dissociation from Grubbs II precatalysts—via facile decoordination of the NHCP phosphino donor of the strained four-membered [RuPNC] chelate systems. Their attempted synthesis from NHCPs and Grubbs-type Ru carbenes revealed addition of an NHCP donor atom (P or C) to the alkylidene fragment, forming a new C-P or C-C bond in five-membered chelate structures. DFT investigations showed that these reactions are controlled kinetically and must not be neglected as important possible deactivation routes in olefin metathesis.